A Snapshot of Antibiotic Resistances in Air Particulate of a Provincial Capital City, Indonesia - Sulfikar Sulfikar; Gotot Junarto; Muhammad Ardhias Syam; Andi Zulfikar Efendy; Mohamad Sahrir; Hilda Ningsih (Syarif Hidayatullah State Islamic University, 2022)
Bacteria may become resistant to antibiotics due to gene mutation or adopting resistance genes from other bacteria via horizontal gene transfer. The existence of toxic substances to bacteria, such as antibiotics, biocides, and heavy metals, may influence the pathway into the genome. This study aimed to detect the presence of antibiotic-resistance bacteria in air particulates in Makassar - a provincial capital located in Indonesia with a low to moderate air quality index (AQI). We determined the correlations between antibiotic resistance (resistance rate, RR) and the heavy-metal concentrations in the air particulates. Air particulate samples were taken from seven locations in the summer (Dry Season: July - August 2019). We analyzed the concentration of As, Cu, and Zn of the air particulates and determined RR from presumptive Escherichia coli (E. coli) isolated from the air particulates. We estimated the RR towards five antibiotics with different mechanisms of action: amoxicillin-clavulanate, chloramphenicol, amikacin, norfloxacin, and trimethoprim. The concentrations of the heavy metals were relatively low, ranging from (µg/Nm3) 0.001 – 0.009 for As, 0.001 – 0.003 for Cu, and 0.007 to 0.783 for Zn. We observed different antibiotic resistance at various locations, ranging from 25% to 100% RR. While there were indications of possible antibiotic resistance patterns in the different areas sampled, the power of this perspective snapshot was insufficient to make statistically valid generalizations.